Slope intercept form : y=mx+b ; where m=slope, b=y-intercept
Passes through (-3, 4) and is perpendicular to the line : y = 3x - 2
**Remember : if a line is perpendicular to something, then you simply take the slope's negative reciprocal**
Slope 1 = 3 (as 3 is in the "m" spot, which is slope).
Slope 2 = -1/3 (because it is the negative reciprocal)
So, plug in the new slope into slope intercept form
y = mx + b → y = -1/3x + b
Remember that it passes through (-3, 4) so we use that to help us find "b" which is our y-intercept.
Plug in -3 for x, and 4 for y
y = mx+b
(4) = -1/3(-3) + b
Simplify.
4= 1 + b
Subtract 1 from both sides.
3 = b → Therefore, b = 3:)
So now we simply plug everything in !!
**Remember : slope = -1/3, b = 3**
y = mx + b
y = -1/3x + 3
~hope I helped!~